(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Technology is drastically changing how people live nowadays and has made a noticeable impact on the lifestyles of young minds. Social networking sites like Facebook, Instagram, Twitter, and others have ingrained themselves as essential components of young people’s life. Since a few years ago, social media usage has significantly increased. The primary goal of this research was to determine what kind of social media marketing messages have an impact on youth minds cognitive, affective, and behavioural attitudinal components. The study conducts research to comprehend the efficacy of social media as a marketing tool and makes an effort to examine the degree to which social media aids in making purchasing decisions in youth. Data were collected through qualitative and quantitative methods. Secondary data were gathered in the form of a literature review and previously published research publications. In quantitative data collection method, the survey through questionnaire utilised a 4-point Likert scale and underwent the necessary internal validation. Total of 104 surveys were gathered to know youth perspective in context to social media marketing. The findings demonstrate that every business uses posts, shares, images, and videos to advertise their services on social media by informing users of new or existing services, offers, events.